Meckel gruber syndrome: a vaginal breech delivery facilitated by encephalocele self-decompression. (18th April 2012) - Mahoney, C; Denton-Cardew, L; Choudhari, Y; Hamer, F
Abstract : Meckel-Gruber Syndrome (MGS) is a rare, lethal, autosomal recessive condition characterised by renal-cystic dysplasia, an encephalocele and polydactyly. A 31 year old female, para 4, including one forceps delivery with cranial decompression of a baby with MGS, attended in her fifth pregnancy. Anomaly scan findings were classical of MGS; termination declined. A 32 week scan showed a large encephalocele with minimal brain tissue, a head circumference of 420mm, severe oligohydramnios and a breech presentation. The delivery options of pre-term induction of labour versus an inevitable caesarean section at term were discussed. The couple opted for induction of a vaginal breech delivery at 34 weeks. Whilst in the active second stage following delivery of the breech the encephalocele self-decompressed under the pressure of pushing and the head was born with no medical intervention. The presenting part in MGS is typically breech as the enlarged head circumference prevents head engagement. Concern regarding passage of the head through the pelvis means those who continue the pregnancy to term either receive a caesarean section - scarring the uterus for a baby that will not survive, or undergo a vaginal breech delivery with cranial decompression – a traumatic event. This case is unique because the encephalocele self-decompressed, reducing maternal distress and avoiding the morbidity associated with a caesarean section. It raises the question of appropriate timing and mode of delivery in these patients, as well as medical awareness that a normal delivery with minimal intervention is possible and could be considered as first line management.